2015
DOI: 10.1103/physrevb.92.045435
|View full text |Cite
|
Sign up to set email alerts
|

One-dimensional Josephson junction arrays: Lifting the Coulomb blockade by depinning

Abstract: Experiments with one-dimensional arrays of Josephson junctions in the regime of dominating charging energy show that the Coulomb blockade is lifted at the threshold voltage, which is proportional to the array's length and depends strongly on the Josephson energy. We explain this behavior as de-pinning of the Cooper-pair-charge-density by the applied voltage. We assume strong charge disorder and argue that physics around the de-pinning point is governed by a disordered sine-Gordon-like model. This allows us to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 31 publications
3
46
0
Order By: Relevance
“…Unexpectedly, the many-body wavefunction becomes localized at high temperatures T ≥ T M BL : T M BL ∼ E range T E J the classical dynamics of the phase is only weakly affected by the Josephson couplings and is almost periodic indicating that the system is non-ergodic in this regime. The low-temperature behavior of a related disordered system has been recently studied in the context of a Bose glass [27,28]. For numerical analysis reported here we have restricted the allowed charging states by −Q ≤ q ≤ Q with Q = 2.…”
Section: Model and Experimental Realizationmentioning
confidence: 99%
“…Unexpectedly, the many-body wavefunction becomes localized at high temperatures T ≥ T M BL : T M BL ∼ E range T E J the classical dynamics of the phase is only weakly affected by the Josephson couplings and is almost periodic indicating that the system is non-ergodic in this regime. The low-temperature behavior of a related disordered system has been recently studied in the context of a Bose glass [27,28]. For numerical analysis reported here we have restricted the allowed charging states by −Q ≤ q ≤ Q with Q = 2.…”
Section: Model and Experimental Realizationmentioning
confidence: 99%
“…Examples include electrical transport in charge density waves (CDW) [1,2], the critical current of magnetic flux lattices [3,4] in type II superconductors, the propagation of magnetic domain boundaries [5] and crack formation in strained materials [6]. It was recently shown that the onset of electrical transport in one-dimensional arrays of Josephson junctions is also determined by the de-pinning of the charge-configuration along the array [7].…”
Section: Introductionmentioning
confidence: 99%
“…The blue and black dotted lines are the classical expression of the depinning theory, Eqn. (3) [21], for differing Λ, which are already substantially reduced from the red solid line that arises from a model based on independent, coherent QPS (rigid quasicharge, i.e. infinite screening length).…”
mentioning
confidence: 96%
“…In this letter we exploit the critical voltage as a probe of localisation (pinning) length N L , which can be determined using a generalised depinning theory. The classical limit of depinning, as applied to JJ chains, has been discussed recently by Vogt et al [21]. Under the assumption of maximal offset charge disorder, with the f i distributed independently for each site, the last term in Eqn.…”
mentioning
confidence: 99%